A Brief Overview of the STP 36th Annual Symposium: Musculoskeletal System. (October 2017) - Gropp, Kathryn E.; Boyle, Michael C.
The title of the 2017 Society of Toxicologic Pathology symposium was "Musculoskeletal System." A brief overview of the General Scientific Symposium is presented herein and describes the topics presented by each speaker. Symposium speakers addressed subjects pertinent to musculoskeletal system toxicologic pathology and drug development ranging from molecular biology of bone homeostasis to regulatory agency requirements and considerations for registration of bone therapeutics. This overview serves to summarize sessions and is intended as a guide to the individual submissions by speakers and symposium contributors.